Cardiac autonomic modulation with donepezil attenuates pyroptosis and mitochondrial dysfunction, leading to improved left ventricular function in trastuzumab-induced cardiotoxicity in rats. (3rd October 2022) - Khuanjing, T; Maneechote, C; Ongnok, B; Prathumsap, N; Arinno, A; Chunchai, T; Arunsak, B; Chattipakorn, S C; Chattipakorn, N
Abstract: Background: Trastuzumab (Trz)-induced cardiotoxicity (TIC) is one of the most common cardiovascular complications of targeted anticancer agents. Cardiac inflammation, cardiac mitochondrial dysfunction, oxidative stress, and cardiac autonomic dysfunction have been identified as potential mechanisms underlying the adverse effects of TIC. Although cardiac inflammation is one of the key mechanisms triggering "pyroptosis", i.e. a new inflammatory form of programmed cell death, the association between TIC and pyroptosis is still largely unknown. Moreover, the modulation of cardiac autonomic activity using an acetylcholinesterase inhibitor (AChE) has been shown to exert cardioprotection in various heart diseases. However, the role of donepezil (DPZ), an AChE, in treating TIC has never been investigated. Purpose: We evaluated the cardioprotective effects of DPZ on left ventricular (LV) function, cardiac mitochondrial function, and pyroptosis in rats with TIC. We hypothesised that DPZ reduces mitochondrial dysfunction and pyroptosis, leading to a reduction of LV dysfunction in TIC rats. Methods: Fifteen male Wistar rats were randomly divided into the control group (n=5, 0.9% normal saline solution, ip) and the Trz group (n=10, 4 mg/kg/day for 7 days, ip). Trz-treated rats were subdivided into the vehicle group (n=5, drinking water, po) and the DPZ group (n=5, 5 mg/kg/day for 7 days, po). At the end of the experiment, echocardiography was performed, and the heart was removed to determine the cardiac mitochondrial function and pyroptosis. Results: Compared with the control group, %LV ejection fraction (%LVEF) was significantly decreased in the Trz group (Fig. 1A). Trz treatment also markedly increased cardiac mitochondrial reactive oxygen species (ROS) production and mitochondrial depolarisation, as indicated by a lower red/green fluorescence intensity ratio (Fig. 1B and C, respectively). Furthermore, Trz induced pyroptosis by increasing NLR family pyrin domain containing 3 (NLRP3) expression and cleaved Gasdermin D/Gasdermin D ratio, compared to the control group (Fig, 1D–F). Notably, DPZ co-treatment potentially reduced mitochondrial ROS production, mitochondrial depolarisation, and pyroptosis (NLRP3 and cleaved Gasdermin D/Gasdermin D ratio), leading to improved %LVEF (Figure 1). Conclusion: DPZ alleviated cardiac dysfunction in TIC rats by improving mitochondrial function and reducing pyroptosis. These findings suggested that DZP could be a novel effective pharmacological intervention against TIC. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1. The National Science and Technology Development Agency Thailand2. The Thailand Research Fund (RGJ)